Psychophysiological Investigation of Combat Veterans with Subthreshold Post-traumatic Stress Disorder Symptoms. Issue 8 (1st August 2016) - Costanzo, Michelle; Jovanovic, Tanja; Norrholm, Seth D.; Ndiongue, Rochelle; Reinhardt, Brian; Roy, Michael J.
ABSTRACT: Objective: Military service members (SMs) with subthreshold combat-related post-traumatic stress disorder (PTSD) symptoms often have clinically significant functional impairment, even though they do not meet full PTSD criteria. We therefore assessed the psychophysical responses of SMs, upon their return from Afghanistan or Iraq, to a fear conditioning paradigm to better understand the biological underpinnings of symptom severity. Methods: Heart rate (HR), skin conductance, electromyography startle, and respiratory rate (RR) were monitored throughout three distinct phases of the paradigm—fear acquisition, fear inhibition, and fear extinction—while plasma catecholamines (epinephrine, norepinephrine, and dopamine) were measured at the end of fear inhibition. Results: Those with higher PTSD symptom severity demonstrated elevations in HR and startle response to danger cues; elevated self-reported depression and anxiety; impaired functional status; poor skin conductance discrimination between danger and safety; and increases in HR and RR during fear extinction. Moreover, an inverse relationship was seen between plasma dopamine and HR during fear inhibition for those with high symptoms. Conclusion: Overall, the physiological responses we observed in our subthreshold PTSD population parallel what has been previously observed in full PTSD, making a case for addressing subthreshold PTSD symptoms in combat veterans.